An Empirical Study on the Development and Assessment of a Supplier Selection Model based on the Analytical Hierarchy Process in the Al Kharj Industrial Sector - Alam, Teg; AlArjani, Ali (Engineering, Technology & Applied Science Research, 2024)
Selecting a supplier is a critical strategic decision for supply chain management in today’s global context. The process involves evaluating suppliers based on core competencies, pricing, delivery timeframes, location, data gathering, and related risks. Suppliers play a crucial role in an organization’s profitability and stability. Finding the most optimal supplier can help industries reduce material expenses and maintain their competitive advantage. The supplier not only impacts the organization’s profit margin but also its economic strength. Choosing a supplier requires considering qualitative and quantitative elements, making it a decision issue with several criteria. This study aims to create and evaluate a supplier selection model using the analytical hierarchy approach, focusing on a specific case study. When selecting the best supplier, it is crucial to consider tangible and intangible elements that may conflict. The supplier selection process considers several criteria, including qualitative and quantitative variables. The proposed methodology involved a literature review and informal interviews with industry experts and academics to establish the selection criteria. "Quality Supplier Co." was chosen due to the paramount importance of their quality. This research will comprehensively analyze several criteria to identify suppliers accurately.